2016
DOI: 10.15376/biores.11.3.singh
|View full text |Cite
|
Sign up to set email alerts
|

Locational determinants for wood pellet plants: A review and case study of North and South America

Abstract: The European Union’s Renewable Energy Directive has led many electricity producers in Europe to use wood pellets in place of fossil fuels. North America has become one of the primary suppliers of wood pellets to Europe. This paper critically examines literature, economic models and data, as well as the supply chain and country risk factors, related to wood pellet production to anticipate where North and South American pellet mills should be built to meet Europe’s demand. Canada, the United States, and Brazil m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The siting of land-based resource-dependent facilities is a non-random process particularly when a large proportion of input expenditures arise from procurement and transportation costs of localized resources, and manufactured products have relatively low value-to-weight ratios 41 . The non-random siting process is well reported in wood pellet industry case studies 42 and optimization applications 43 .…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The siting of land-based resource-dependent facilities is a non-random process particularly when a large proportion of input expenditures arise from procurement and transportation costs of localized resources, and manufactured products have relatively low value-to-weight ratios 41 . The non-random siting process is well reported in wood pellet industry case studies 42 and optimization applications 43 .…”
Section: Methodsmentioning
confidence: 98%
“…The estimation of the probability of an NFI plot in our sample ( n ) being within the procurement radius of a wood pellet mill was given by: where R takes on value of ‘1’ if the i th plot was located within the procurement radius of a wood pellet mill at any point during our sample period, and ‘0’ otherwise. Industry location theory and empirical evidence were our basis for choosing PSM covariates in vector M i 42 , 48 , 49 . These included: (a) Geodesic distance to nearest port trading forest products, (b) county’s road density, (c) land ownership (private or other), (d) geodesic distance to nearest wood-using power plant, (e) geodesic distance to nearest pulp mill, and (f) state- and (g) forest group type-specific effects.…”
Section: Methodsmentioning
confidence: 99%
“…The so-called new-bio-based development is emerging mostly via small-and medium-enterprises, which are striving for success among the myriad of challenges inherent to new businesses, along with uncertainties specific to the bio-based industry. Factors such as continuous development of new technologies (i.e., technologies at different readiness levels) (Gonzalez et al 2011a,b), uncertain product prices (de Assis et al 2017a(de Assis et al ,b, 2018, and geopolitical dynamics (Goh et al 2013;Singh et al 2016), in combination with unique uncertainties found in the bio-based sector, such as variability in feedstock composition (Treasure et al 2014) and feedstock availability (Gonzalez et al 2011c), add more complexity to the already intricate investment decision-making environment of the bio-based sector. In order to reduce the chances of project failure and maximize value, it is crucial to incorporate risk assessment into the decision-making processes (Brauers 1986;Curtis and Carey 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of EU RED National Action Plans triggered the establishment of new manufacturing facilities pelletizing wood fibers across the US coastal southeast [14,15]. It is important to note that EU RED National Action Plans do not target forests of any particular region, rather, the supply of US wood pellets developed organically partly due to cost competitive and comparative production advantages [16].…”
Section: Us Wood Pellet Industry Expansionmentioning
confidence: 99%